2021
DOI: 10.1007/s00709-021-01677-3
|View full text |Cite
|
Sign up to set email alerts
|

The molecular identity of the characean OH− transporter: a candidate related to the SLC4 family of animal pH regulators

Abstract: Characeae are closely related to the ancient algal ancestors of all land plants. The long characean cells display a pH banding pattern to facilitate inorganic carbon import in the acid zones for photosynthetic efficiency. The excess OH−, generated in the cytoplasm after CO2 is taken into the chloroplasts, is disposed of in the alkaline band. To identify the transporter responsible, we searched the Chara australis transcriptome for homologues of mouse Slc4a11, which functions as OH−/H+ transporter. We found a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The internodal cells acidify their surface either directly or via carbonic anhydrase to help facilitate the conversion of to membrane-permeable CO 2 for increasing photosynthetic efficiency ( Eremin et al, 2019 ). In order to maintain pH homeostasis of the cytoplasm, the proton efflux is balanced by either influx of H + or efflux of OH − ( Quade et al, 2022 ). The resulting pattern of alternating acid and alkaline regions or “bands” helps maintain metabolism ( Beilby and Bisson, 2012 ).…”
Section: The Cell Biology Of Charophytesmentioning
confidence: 99%
“…The internodal cells acidify their surface either directly or via carbonic anhydrase to help facilitate the conversion of to membrane-permeable CO 2 for increasing photosynthetic efficiency ( Eremin et al, 2019 ). In order to maintain pH homeostasis of the cytoplasm, the proton efflux is balanced by either influx of H + or efflux of OH − ( Quade et al, 2022 ). The resulting pattern of alternating acid and alkaline regions or “bands” helps maintain metabolism ( Beilby and Bisson, 2012 ).…”
Section: The Cell Biology Of Charophytesmentioning
confidence: 99%
“…As confirmed in two other studies, SLC4A11 does not transport borate [ 11 , 16 ]. In addition, there is an inconsistent demonstration of Na + -dependent and -independent electrogenic H + flux by SLC4A11 in corneal endothelial cells [ 10 ] and in SLC4A11 transfected cell lines [ 3 , 10 , 12 , 16 , 53 , 54 , 55 ]. Consistent with the inward H + flux from SLC4A11, mouse corneal endothelial cell lines from the SLC4A11 KO have a significantly higher pHi i than WT cells when perfused in a low buffering capacity bicarbonate-free ringer.…”
Section: Ion Transport Function Of Slc4a11mentioning
confidence: 99%
“…Myers et al [ 54 ], also using transfected oocytes, showed enhanced Na + -independent H + conduction, but concluded that SLC4A11 was activated by alkaline pH. Moreover, the H + conductance of SLC4A11 was found to be steepest at pH 8.5 and it was found that mutants can shift the optimum pKa [ 55 ]. In summary, from these studies, it appears that SLC4A11 provides H + conductance that can be either Na + dependent or independent, is sensitive to NH 4 Cl, and is stimulated by alkaline pH.…”
Section: Ion Transport Function Of Slc4a11mentioning
confidence: 99%
“…These macroscopic multicellular complex algae inhabit freshwater, as well as brackish and saline environments worldwide (Khan 1991). The relevance of Charophyceae for evolutionary and applied research areas, such as ecophysiology, paleoecology, ontogenesis, molecular and comparative genomics (Beilby 2019, Vicente et al 2019, Holzhausen et al 2022b, Quade et al 2022) peaked in the establishment of the freshwater alga Chara braunii C.C. Gmel.…”
Section: Introductionmentioning
confidence: 99%